1967
DOI: 10.1111/j.1432-1033.1967.tb00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oleic Acid on the Oxidation and Gluconeogenesis from [1‐14C]Pyruvate in the Perfused Rat Liver

Abstract: Gluconeogenesis from [l-14C]pyruvate in the perfused liver from fasted rats was stimulated by oleic acid as indicated by an increase in medium glucose, liver glycogen and specific activity of medium [14C]glucose. A balance of carbon from pyruvate revealed that in the presence of oleic acid 2 moles of pyruvate were utilized for each mole of glucose synthesized in contrast to a ratio 4: 1 without fatty acid. From this and 14C0, data it is concluded that oleic acid inhibited pyruvate oxidation markedly. Glucagon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
3

Year Published

1969
1969
1972
1972

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(29 citation statements)
references
References 23 publications
(24 reference statements)
6
20
3
Order By: Relevance
“…Confirming previous work [7], the addition of oleate together with pyruvate increases glucose formation approximately 2-fold in comparison to livers perfused with pyruvate alone ( Table 4). The efficiency of pyruvate conversion to glucose is increased by oleate as the ratio of C3 units to glucose decreases (Table 4).…”
Section: Effect Of Oleate On the Metabolism Of Pyruvate In The Presensupporting
confidence: 76%
See 2 more Smart Citations
“…Confirming previous work [7], the addition of oleate together with pyruvate increases glucose formation approximately 2-fold in comparison to livers perfused with pyruvate alone ( Table 4). The efficiency of pyruvate conversion to glucose is increased by oleate as the ratio of C3 units to glucose decreases (Table 4).…”
Section: Effect Of Oleate On the Metabolism Of Pyruvate In The Presensupporting
confidence: 76%
“…The sources of animals and materials, the technique of perfusion [20], and the methods of medium analysis have been described in detail [7,20]. Samples of the liver perfusate for free fatty acid analysis were centrifuged for 2 min in a micro-centrifuge (Eppendorf Centrifuge 3200, Netheler and Hinz, Hamburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose formation from pyruvate (0.83 pmole x g-1 x min-1) in the present experiments was slightly lower than that reported by Ross et al [13] although considerably higher than that reported by Teufel et al [20]. A significant portion of pyruvate metabolized (approx.…”
Section: Effects Of Glucagon and B~~a D O -3 'contrasting
confidence: 56%
“…Similarly t,o fatty acids, glucagon enhances glucose formation from lactate [10-18], pyruvate [12][13][14][17][18][19][20] and alanine [12,19]. The role of cyclic adenosine 3': 5'-monophosphate (Ado-3' : 5'-P) as mediator of glucagon action in liver has been extended to its enhancement of gluconeogenesis [17,18,21,22].…”
mentioning
confidence: 99%